3D crustal velocity and Vp/Vs structures beneath Southeast Anatolia and their geodynamic implications - Salah, M.K.; Şahin, Ş. (Геофизический журнал, 2019)
We applied a seismic tomography method to arrival time data generated by local crustal earthquakes in Southeast Anatolia to study the shallow, three-dimensional, velocity and VP/VS structures beneath the area.